2018
DOI: 10.1186/s12951-018-0394-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nanoparticle surface functionalization on the protein corona and cellular adhesion, uptake and transport

Abstract: BackgroundUpon ingestion, nanoparticles can interact with the intestinal epithelial barrier potentially resulting in systemic uptake of nanoparticles. Nanoparticle properties have been described to influence the protein corona formation and subsequent cellular adhesion, uptake and transport. Here, we aimed to study the effects of nanoparticle size and surface chemistry on the protein corona formation and subsequent cellular adhesion, uptake and transport. Caco-2 intestinal cells, were exposed to negatively cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 53 publications
3
55
0
Order By: Relevance
“…In general, the AgNPs content in the cellular fraction appeared to be higher in the (LA) AgNPs samples than in the (Cit) AgNPs samples, following exposure to pristine AgNPs. The difference in the cellular total Ag content between (LA) and (Cit) AgNPs could be explained by possible formation of different types of protein coronas on the AgNPs due to their differences in surface chemistry, as previously described for AgNPs and other NPs (Abdelkhaliq et al 2018;Lesniak et al 2012;Monteiro-Riviere et al 2013;Tenzer et al 2013). Another factor influencing the interaction of AgNPs with cells could be the stability of the coating which might be affected by the ionic strength, protein content, or pH of the medium .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In general, the AgNPs content in the cellular fraction appeared to be higher in the (LA) AgNPs samples than in the (Cit) AgNPs samples, following exposure to pristine AgNPs. The difference in the cellular total Ag content between (LA) and (Cit) AgNPs could be explained by possible formation of different types of protein coronas on the AgNPs due to their differences in surface chemistry, as previously described for AgNPs and other NPs (Abdelkhaliq et al 2018;Lesniak et al 2012;Monteiro-Riviere et al 2013;Tenzer et al 2013). Another factor influencing the interaction of AgNPs with cells could be the stability of the coating which might be affected by the ionic strength, protein content, or pH of the medium .…”
Section: Discussionmentioning
confidence: 90%
“…Nanomaterials are used in a broad range of products and applications such as textiles, medical devices, water disinfection, personal hygiene and food products (Abdelkhaliq et al 2018;Chaudhry et al 2008;Imai et al 2017;Lichtenstein et al 2015). Because of the antimicrobial potential of silver nanoparticles (AgNPs), they are amongst the most frequently used nanoparticles (NPs) in food associated products (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Both sulfonated and carboxylated PS NPs (50 nm) have negatively charged surfaces. Although the composition of the protein corona isolated from these PS NPs was the same, some proteins, including A2M, AFP, APOA2, APOH, and HBB were significantly less adsorbed onto the sulfonated PS NPs (Abdelkhaliq et al, 2018). In another study, it was found that negatively charged poly(methacrylic acid)-decorated iron oxide NPs (10 nm) tended to adsorb more proteins from fetal bovine serum (FBS) than were adsorbed by citric acid-decorated iron oxide NPs (Mekseriwattana et al, 2019).…”
Section: Surface Chargementioning
confidence: 97%
“…This leads to a reduction of the absolute ζ potential value which results in a more neutral surface charge and therefore less particle adhesion to the cell membrane and decreased cell uptake (Hsu & Juliano, 1982). On the other hand, PEG chains impair the binding of serum proteins and therefore hamper the building of a protein corona, which forms within seconds upon intravenous injection on the surface of the nanoemulsion-droplets and promotes the uptake by phagocytic cells (Abdelkhaliq et al, 2018). The underlying mechanism for this protein rejection is assumed to be a spring-like acting of the PEG molecules: Binding of serum proteins to PEGylated particles leads to a compression of the PEG chains which is then followed by a rejection of the proteins, at least for PEG chains with a size~2000 kDa (Lee, Park, & Lee, 1991;Peracchia, Vauthier, Passirani, Couvreur, & Labarre, 1997).…”
Section: Manufacturing Of Targeted Pfcsmentioning
confidence: 99%